2014
DOI: 10.1371/journal.pone.0113888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feedstock and Pyrolysis Temperature on Biochar Adsorption of Ammonium and Nitrate

Abstract: Biochar produced by pyrolysis of biomass can be used to counter nitrogen (N) pollution. The present study investigated the effects of feedstock and temperature on characteristics of biochars and their adsorption ability for ammonium N (NH4 +-N) and nitrate N (NO3 −-N). Twelve biochars were produced from wheat-straw (W-BC), corn-straw (C-BC) and peanut-shell (P-BC) at pyrolysis temperatures of 400, 500, 600 and 700°C. Biochar physical and chemical properties were determined and the biochars were used for N sorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
265
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 498 publications
(315 citation statements)
references
References 38 publications
(65 reference statements)
46
265
1
3
Order By: Relevance
“…Compared to peat, the longer decomposition half-life of high-temperature BCs such as the one in this study, and the potential of nutrient ions to bind to BC (Gai et al, 2014;Lehmann and Joseph, 2015;Yao et al, 2012) and re-solubilize when applied to soils (Joseph et al, 2013;Yao et al, 2013) raises the possibility of re-using BC-based substrates as fertilizers.…”
Section: Additional Advantages and Possibilities Of Bc Substitution Fmentioning
confidence: 88%
“…Compared to peat, the longer decomposition half-life of high-temperature BCs such as the one in this study, and the potential of nutrient ions to bind to BC (Gai et al, 2014;Lehmann and Joseph, 2015;Yao et al, 2012) and re-solubilize when applied to soils (Joseph et al, 2013;Yao et al, 2013) raises the possibility of re-using BC-based substrates as fertilizers.…”
Section: Additional Advantages and Possibilities Of Bc Substitution Fmentioning
confidence: 88%
“…Similarly, Gai et al (2014) reported a decrease in biochar's ability to remove ammonium after being washed in deionised water. Wang et al (2015) found that the ammonium adsorption capacity of biochar did not change after activation with H2O2 unless the pH of activated biochar was adjusted from 3.7 to 7.…”
Section: Ammonium Removalmentioning
confidence: 95%
“…Biochar has been suggested as a sorbent for ammonium (TaghizadehToosi et al, 2012a;Hale et al, 2013;Gai et al, 2014;Carey et al, 2015;Cui et al, 2016), orthophosphate (Hollister et al, 2013;Sarkhot et al, 2013;Xu et al, 2014) and organic contaminants (Ahmad et al, 2014;Mohan et al, 2014;Wang et al, 2015b) removal from various wastewaters. Chemical activation of biochar has been shown to increase the oxygen-containing functional groups (Xue et al, 2012;Wang et al, 2015a) which affects the cation sorption on biochar, and orthophosphate removal due to cation bridge bonding (Lin et al, 2012;Qian et al, 2013).…”
Section: Thesis Outline and Experimental Approachmentioning
confidence: 99%
See 2 more Smart Citations